PENGARUH TANGGUNG JAWAB SOSIAL PERUSAHAAN, PROFITABILITAS, DAN TINGKAT UTANG TERHADAP PENGHINDARAN PAJAK (Studi Kasus pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Nathania Najwa Aureliya Risdiana; Endang Kiswara (Diponegoro Journal of Accounting, 2026)
This research aims to analyze the effect of corporate social responsibility, profitability, and leverage on tax avoidance in mining companies listed on the Indonesia Stock Exchange during 2022–2024. Mining sector companies were selected because this sector has significant economic, social, and environmental impacts, making the implementation of corporate social responsibility important and subject to special attention from the government. However, during the 2022–2024 period, the number of active taxpayers in the mining sector increased, while tax revenue realization tended to decline.This study employed a quantitative method. The data used were secondary data obtained from annual reports and sustainability reports of companies published through the Indonesia Stock Exchange. The research sample consisted of 47 mining companies. The data analysis method used was panel data regression with the assistance of EViews 13.The results showed that corporate social responsibility had no significant effect on tax avoidance. Meanwhile, profitability had a positive effect on tax avoidance, whereas leverage had a negative effect on tax avoidance.